PEMBELAJARAN MORAL MELALUI MATA KULIAH HUKUM ISLAM - Marjuki Marjuki (Jurnal Kependidikan, 2008)
The main problems  in  this study  are how  moral  learning  is achieved by the Islamic Law subject in the PPKN Department (now: PKnH) of the Social Science Faculty (now: FISE) ofYogyakarta State University and what factors  influence moral learning in the Islamic Law subject. The study is qualitative and descriptive survey research. The data were obtained by questionnaires and interviews with the students taking the Islamic Law subject. The results show that Islamic law learning is one of the moral learning. The moral learning achieved through the Islamic Law subject manifests in many ways, i.e.: 1) Almost all instructional topics contain moral values, 2) Learning strategies which endorse moral problems are the dialogue and speech method and the discussion  method, and 3)  The assessment process  which endorses moral problems is that related to the students' behaviours and attitudesfrom the beginning until the end of the learning process. The main factors   obstructing  the  moral  learning  are: 1)  The  basic competence of students in PPKN is heterogeneous, 2)  The students' interest in moral problems  is not high, and 3)  Moral  learning is difficult.